Accurate recognition of colorectal cancer with semi-supervised deep learning on pathological images - Gang Yu (Nature Portfolio, 2021)
Machine-assisted recognition of colorectal cancer has been mainly focused on supervised deep learning that suffers from a significant bottleneck of requiring massive amounts of labeled data. Here, the authors propose a semi-supervised model based on the mean teacher architecture that provides pathological predictions at both patch- and patient-levels.